Pulse length dependence on the decay of the integrated pulse energy/Integruoto impulso energijos slopimo priklausomybė nuo skirtingų impulso ilgių - Stauskis, Vytautas (Journal of Civil Engineering and Management, 2000)
The paper deals with the influence of the pulse length on the decay of the sound field energy. Six pulse lengths –  2000, 2500, 3000, 3500, 4000 and 4500 ms – were selected for investigations. Investigations show that a 2500 ms pulse is too short to correctly assess the background noise time interval. Such pulse length is not suitable for experiments. 3000 ms is the right length, while 3500 ms may be too long, resulting in errors of measurement results. When the pulse length increases to 4000 ms, the decay starting from 2000 ms is different from the pulse length 2500 ms and 3000 ms. Background noise starts from 2300 ms for these pulses, while for a 4000 ms pulse it starts from 3200 to 3300 ms. The length of 4500 ms is completely not suitable for investigations because the background noise zone starts very early, ie at 1800 ms, while for a short 2500 ms pulse it starts much later, after 2300 ms. While investigating energy decay, it is important to determine the maximum decay. At 63 Hz the sound field decay is almost uniform till – 18 dB. Later the decay character is different. The decay of the longest (4500 ms) and the shortest (2500 ms) pulse after – 18 dB is very steep and reaches – 30 dB. However, the decay is influenced by the background noise. Thus the shortest and the longest pulses are not suitable for the lowest frequencies. The greatest energy decay is characteristic of the 3000 ms pulse. After 1700 ms energy decreases to – 30 dB. Thus at this frequency one may measure the echoing time while approximating decay from 0 to – 20 dB. As the frequency increases, the results change. At 100 Hz the energy decays by – 35–37 dB at pulse lengths of 2500 ms and 4000 ms. The greatest decay of – 42 dB is produced by the longest pulse 4500 ms though this arouses certain doubts. Then the echoing time may be measured from 0 to – 30 dB. At 125 octave frequency the smallest maximum decay of – 40 dB is observed with the shortest pulse (2500 ms), while the largest one – 50 dB is produced by the longest pulse (4500 ms). Thus standard echoing time may be measured for this frequency. In the frequency range of 250–2000 Hz, the maximum energy decay is sufficient and amounts to – 50–60 dB. At 4000 Hz the final part of decay is strongly dependent on the pulse length although, as the decay is about – 55 dB in all cases, the standard echoing time may be measured correctly. Pulse length is important only for the calculation of the low-frequency echoing time. At 63–100 Hz the best maximum decay is seen with the pulse 3000 ms long, while at 125 Hz and over the best pulse lengths are from 3000 to 4000 ms. When the hall contains audience and tapestries are on the walls, the energy decay is almost uniform at the pulse lengths of 2000 to 2800 ms. In this case a better decay is obtained with the longest pulse of 2800 ms.Article in Lithuanian.First Published Online: 26 Jul 2012